Advancing sustainability with blockchain-based incentives and institutions - Smajgl, Alex; Schweik, Charles M. (Frontiers in Blockchain, 2022)
Despite significant efforts over many decades, humanity faces daunting challenges in the governance, management and sustainability of natural resources. Perhaps the most obvious is our global inability to collectively act and control or reduce greenhouse gases that are warming the planet. Another example, occurring at finer geographic scales, is the overuse of groundwater aquifers. Institutions – defined in Political Science and Economics as formal and informal rules that guide and incentivize socio-economic activities – are humanity’s general approach toward addressing these and other environmental challenges. Institutional arrangements typically specify whom they apply to, under what circumstances, and what penalty the breaking of the rule involves. Effective institutional design requires the ability to properly incentivize human behavior in the context of socio-economic systems, and establish systems to monitor behavior and sanction when rules are broken. From time to time, technological advances come along that complement institutional designs and improve our ability to incentivize and monitor behavior. We believe that the invention of Blockchain or Distributed Ledger technology – increasingly touted as the beginning of the fourth industrial revolution– could provide new ways to incentivize the behavior of resource users, establish innovative monitoring capacity, and help to avoid corrupt governmental behavior. In this Perspective article, we summarize Proof-of-Stake Blockchain technology and provide two examples – deforestation and groundwater management – to describe how this new revolution could provide new solutions for the sustainable management of natural resources at local to global scales.